THE LEADERSHIP STYLES OF EFFECTIVE NURSE MANAGERS AND THEIR IMPACT ON STAFF MORALE - ‏ Atheer Karidi Aldafeeri, ‏Dalal Mohammad Alshammari, ‏Norah Mohammad Alshammari, ‏Eman Kuwaysaldhfeeri, ‏Monefa Eissa Mosheb Aldhafeeri, ‏Mardaiah Salem Al-Anizi, ‏Aisha Raffasal-Daffery, Mona Ibrahim Alenzi, Aishahmoflehalrashidi, Latifah Awadalrashee,; Mashaalbadahalsahli, Amal Farhan Alharbi, Dhayah Deherb Alshammri, Ahoud Hammad Alshammari, Haya Mubarak Aldossri, ‏Salama Aish Al-AniziAbstract, (Chelonian Research Foundation, 2022)
This systematic review sought to analyze and consolidate the findings of studies that investigate the correlation between the leadership practices of nurse managers and the job engagement of staff nurses in hospital settings. The objective was to provide suggestions for enhancing these practices and suggest areas for further study. A comprehensive evaluation was undertaken to discover research that has been published and registered in well-known databases such as PubMed, CINAHL, PsycINFO, Embase, EMCare, and Eric. Three primary leadership style themes were found, and they exhibited statistically significant direct and indirect correlations with nurses' job engagement: relationally oriented, task-focused, and absence of leadership. The assessment of work engagement primarily focused on commitment, absorption, and vigor. The impact of different leadership styles on work engagement was discovered to be influenced by several factors. These factors include trust in the leader, environmental resources like structural empowerment, six work-life areas (workload, control, values, community, rewards, and fairness), person-job fit, organizational support, leader-member exchange, and personal resources such as self-efficacy and decision authority. This research identified a noteworthy association between a good leadership style shown by nurse managers and the level of job engagement displayed by registered nurses. The findings of this research indicate that the level of engagement among nurses may be enhanced by adopting relational leadership behaviors. The results of this research will be valuable for the development of suitable leadership styles for nurse leaders, enhancing their work conditions, and designing leadership training programs. When creating treatments for staff nurses, it is crucial to recognize the indirect impacts of nurse leaders' leadership styles and the elements that mediate their influence on job engagement. Keywords: Nurses, leadership, nurse managers, staff morale, training programs.